Demographic analysis of hearing impairment based on various parameters in patients with cochlear implant - Riaz, Isma; Amir Rashid,; Asifa Majeed, (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse the demographic and clinical variables in children having undergone cochlear implant surgery because of deafness. Method: The cross-sectional study was conducted from January to November 2022at the Centre for Research in Experimental and Applied Medicine laboratory of the Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi, Pakistan, in collaboration with the Ear, Nose and Throat Department of Combined Military Hospital, Rawalpindi, and comprised children of eith gender aged up to 10 years who had received cochlear implant. Data was collected through questionnaire-based detailed interviews. Syndromic Hearing Loss, Non-Syndromic Hearing Loss, and Acquired Hearing Loss were identified among the subjects. Data was analysed using SPSS 22. Results: Of the 250 cases, 147(58.8%) were boys, 146(58.4%) were aged 0-5 years, 219(87.6%) had prelingual onset of disease, and 202(80.8%) had a non-progressive disease course. In 203(81.2%) cases, normal developmental milestones were seen. Parental consanguinity was observed in 219(87.6%) cases. However, 63(25.2%) patients had a first-degree relative who had a history of deafness. In 170(68%) cases, hearing loss was hereditary, whereas in 80(32%) it was acquired. Meningitis was the most commonly identified risk factor 55(68.75%). Acquired risk factors and family history had significant association with hearing loss (p<0.05). Speech perception significantly improved in all 219(100%) patients with prelingual hearing loss who underwent cochlear implantation. Conclusion: Majority of the cases were found to be male, had a prelingual disease onset and a non-progressive disease course. Family history was a significant factor, while meningitis was the most common acquired cause of hearing loss. Key Words: Autosomal recessive hearing loss, Hereditary hearing loss, Non-syndromic hearing loss, Sensorineural hearing loss.